Fusobacterium nucleatum Extracellular Vesicles Modulate Gut Epithelial Cell Innate Immunity via FomA and TLR2 - Martin-Gallausiaux, Camille; Malabirade, Antoine; Habier, Janine; Wilmes, Paul (Frontiers in Immunology, 2020)
Extracellular vesicles (EVs) derived from the gut microbiota are largely uncharacterised and their impacts on host intestinal physiology remain unresolved. Here, we isolated EVs from F. nucleatum nucleatum for detailed characterisation. Our analyses highlight the presence of the outer membrane protein porin FomA on EVs. Besides, we evaluated the impact of EVs on human intestinal epithelial cells (IECs) in a non-inflammatory context. Our results show no detrimental impact on the epithelial barrier. No internalisation of EVs was observed. Moreover, we demonstrate that F. nucleatum EVs trigger innate immunity of IECs by promoting NF-κB activation via the dynamin-mediated endocytosis. The NF-κB activation was found to be TLR2-dependent yet, TLR4 was dispensable. Using competitive binding assays, we establish that FomA is involved in the NF-κB response. Taken together, our data indicate that EVs induce effects similar to those observed with whole F. nucleatum bacteria on IECs. In particular, our study highlights the role of TLR2 and FomA as major modulators of the gut epithelium immune responses to F. nucleatum.